PENERAPAN MODEL PEMBELAJARAN REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI GERAK DAN GAYA KELAS VIII-5 SMP NEGERI 6 MEDAN TAHUN AJARAN 2018/2019 - Yanti Yanti (JGK (Jurnal Guru Kita), 2022)
Application of a Realistic Learning Model to Improve Science Learning Outcomes Material of Motion and Style for Class Viii-5 SMP Negeri 6 Medan Academic Year 2018/2019. The purpose of carrying out this research is to find out that the application of Realistic Science Learning can improve student learning outcomes in the material of Motion and Style in class VIII-5 of SMP Negeri 6 Medan in the 2018/2019 Academic Year. This study used a type of action research (PTK) consisting of pre-cycle and 3 (three) class cycles. The location of this research was carried out at SMP Negeri 6 Medan. Data collection techniques using student learning outcomes tests and observations made are observations of all activities and changes that occur when the action is given, and data analysis techniques with comparative descriptive analysis. Based on the results of the study, after being given action in cycle I, classical learning completeness was obtained by 25%, while in the second learning achievement test, classical learning mastery was obtained by 68.75% or an increase of 43.75% from cycle I, and on the results test learning III obtained classical learning mastery of 87.50% or an increase of 18.75% from cycle II. So that a realistic science approach to the material of Motion and Style can improve the science learning outcomes of class VIII-5 students of SMP Negeri 6 Medan. It can be concluded that through realistic learning on the material Motion and Style students in class VIII-5 at SMP Negeri 6 Medan feel enthusiastic in learning because the questions given are questions related to everyday life and each student is active and free to determine the solution of each problem according to their respective thoughts. Furthermore, the teacher and students draw conclusions from a formulation of a concept or principle from the problem at hand.